Boosting Interfacial Charge-Transfer Kinetics for Efficient Overall CO2 Photoreduction via Rational Design of Coordination Spheres on Metal–Organic Frameworks - Fang, Zhi-Bin; Liu, Ting-Ting; Liu, Junxue; Jin, Shengye; Wu, Xin-Ping; Gong, Xue-Qing; Wang, Kecheng; Yin, Qi; Liu, Tian-Fu; Cao, Rong; Zhou, Hong-Cai (Journal of the American Chemical Society, 2020)
The recombination of electron–hole pairs severely detracts from the efficiency of photocatalysts. This issue could be addressed in metal–organic frameworks (MOFs) through optimization of the charge-transfer kinetics via rational design of structures at atomic level. Herein, a pyrazolyl porphyrinic Ni-MOF (PCN-601), integrating light harvesters, active catalytic sites, and high surface areas, has been demonstrated as a superior and durable photocatalyst for visible-light-driven overall CO2 reduction with H2O vapor at room temperature. Kinetic studies reveal that the robust coordination spheres of pyrazolyl groups and Ni-oxo clusters endow PCN-601 with proper energy band alignment and ultrafast ligand-to-node electron transfer. Consequently, the CO2-to-CH4 production rate of PCN-601 far exceeds those of the analogous MOFs based on carboxylate porphyrin and the classic Pt/CdS photocatalyst by more than 3- and 20-fold, respectively. The reaction avoids the use of hole scavengers and proceeds in a gaseous phase which can take full advantage of the high gas uptake of MOFs. This work demonstrates that the rational design of coordination spheres in MOF structures not only reconciles the contradiction between reactivity and stability but also greatly promotes the interfacial charge transfer to achieve optimized kinetics, providing guidance for the design of highly efficient MOF photocatalysts.